A Review of the Legal, Regulatory, and Economic Barriers to Wind Energy Development in Iraq - Ali, Taghreed (Journal of Renewable Energy and Mechanics, 2026)
Iraq, a nation heavily reliant on hydrocarbon resources, faces a severe and persistent electricity crisis, necessitating a strategic shift towards diversifying its energy mix. Wind energy presents a compelling opportunity to address these challenges, offering a clean, sustainable, and potentially abundant power source. However, the large-scale development of wind energy in Iraq is significantly hampered by a complex interplay of legal, regulatory, and economic barriers. This review paper meticulously examines these impediments, drawing upon extensive academic literature, policy documents, and expert analyses. Legally, the absence of enacted comprehensive renewable energy legislation, coupled with ambiguities arising from unresolved hydrocarbon legislation and complexities in land ownership, creates an uncertain investment climate. Regulatory hurdles stem from an evolving and often unclear framework, a lack of transparent guidelines for licensing and grid connection, pervasive bureaucratic inefficiencies, and insufficient inter-ministerial coordination. Economically, high initial investment costs, fierce competition with heavily subsidised fossil fuels, limited access to financing, and an unstable macroeconomic environment deter private sector participation. The pervasive issue of corruption further exacerbates these challenges, increasing risks and costs for potential developers.